Accidental Awareness During General Anesthesia in an Anesthetist: A Patient–Clinician Perspective - Ranjith Raghavan Thampi (Clinical Case Reports, 2026)
ABSTRACT Accidental awareness during general anesthesia is multifactorial and may occur despite apparently stable physiological parameters and in the absence of neuromuscular blockade. Reliance on clinical signs alone may be insufficient to assess hypnotic depth, highlighting the importance of appropriate monitoring, vigilance, and structured postoperative assessment.